Highly specific and reliable in vitro diagnostic analysis of memory T and B lymphocytes in a Swiss cohort of COVID-19 patients (Swiss Medical Weekly, 2021)
The SARS-CoV-2 pandemic has claimed many lives and disrupted the quality of life of most individuals. Diagnostic tests not only serve to confirm past exposure but can provide information crucial for guiding healthcare options for patients. Current diagnostic tests for the presence of the SARS-CoV-2 virus or anti-spike protein antibodies do not address the question whether longer lasting cellular immunity is mounted in most individuals. Using an activation marker flow cytometric immunoassay (SARS-CoV-2 lymphocytes analysis), we showed that both CD4+/CD8+ T cell and B cell activation differ between naïve and infected individuals up to 11 months after infection. On the basis of the specificity of this diagnostic tool for detecting both SARS-CoV-2-experienced T and B cells, we propose that this assay could benefit immunocompromised individuals who are unable to mount sustained antibody responses, by determining cellular immunity as possible partial protection, and for studying immune correlates of protection – thereby increasing knowledge of COVID-19 in a wider range of patient groups.